Evaluation Of Retinal Nerve Fibre Layer and Macular Thickness In Patients With Hypertensive Disorder In Pregnancy - Kahar, Mas Edi Putriku Intan Ab (2021)
Objective: Evaluate retinal nerve fibre layer (RNFL) and macular thickness in patients with hypertensive disorder in pregnancy (HDP) compared to healthy pregnant control in third trimester. Methodology: Comparative cross-sectional study conducted in Hospital Universiti Sains Malaysia with 200 HDP participants and 50 controls recruited. Clinically stable participants who fulfilled criteria with normal ocular examinations were subjected to optical coherent tomography (OCT) of the right eye. RNFL and macular thickness were evaluated and analysed using SPSS 26.0. Results: Thinner mean RNFL and macular quadrants in HDP groups compared to control were observed; after controlling potential cofounders. Pre-eclampsia showed significant thinning at average and superior RNFL quadrants while, gestational hypertension group showed thinning at average, superior and inferior RNFL regions. Chronic hypertension group showed thinner average RNFL, while chronic hypertension with superimposed pre-eclampsia showed significant thinning at average and superior RNFL quadrants. Thinner outer temporal macular region observed in both gestational and chronic hypertension with superimposed pre-eclampsia groups with mean of 251.00μm and 251.11μm respectively. The latter group also showed thinner outer inferior macular of 259.53μm. Regression analysis between blood pressure (BP) and number of antihypertensive medications with average RNFL and macular thickness showed no significant associations. Conclusion: Mean RNFL thickness was significantly lower in the all HDP groups while macular thickness was significantly lower in the gestational hypertension and chronic hypertension with superimposed pre-eclampsia group. Blood pressure and number of medications showed no significant associations with RNFL and macular thickness.